2022
DOI: 10.1108/bij-10-2021-0585
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the adoption of integrated sustainable-green-lean-six sigma-agile manufacturing system (ISGLSAMS): a literature review

Abstract: PurposeScarcity of resources, ecological imbalance, global warming, rising energy prices and the ever-changing need for variety have attracted the government and manufacturers for sustainable development of the industries. The integrated sustainable-green-lean-six sigma-agile manufacturing system (ISGLSAMS) provides a solid platform for meeting both the customers’ variety needs and business sustainability requirements. Many organizations opted for ISGLSAMS, but still due to various barriers organizations are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 240 publications
0
6
0
Order By: Relevance
“…, 2022; Condé et al. , 2023; Hariyani and Mishra, 2022). It offers benefits such as increased inventory turnover, capacity, customer satisfaction, sales, return on assets, labor productivity, product quality, on-time delivery, overall productivity, financial performance, market performance, competitive market position and various intangible advantages (Gijo et al.…”
Section: Lean Six Sigma-a Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2022; Condé et al. , 2023; Hariyani and Mishra, 2022). It offers benefits such as increased inventory turnover, capacity, customer satisfaction, sales, return on assets, labor productivity, product quality, on-time delivery, overall productivity, financial performance, market performance, competitive market position and various intangible advantages (Gijo et al.…”
Section: Lean Six Sigma-a Literature Reviewmentioning
confidence: 99%
“…The voice of the customer is integrated into the definition of lean value. Lean manufacturing reduces work in process, cycle time, lead time, conversion costs, space requirements, equipment downtime, waste and overall costs (Adeinat et al, 2022;Cond e et al, 2023;Hariyani and Mishra, 2022). It offers benefits such as increased inventory turnover, capacity, customer satisfaction, sales, return on assets, labor productivity, product quality, on-time delivery, overall productivity, financial performance, market performance, competitive market position and various intangible advantages (Gijo et al, 2018;Panayiotou et al, 2022).…”
Section: Lean Six Sigma Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart manufacturing processes enable real‐time monitoring, data‐driven decision‐making, and predictive maintenance, leading to decreased downtime and increased productivity (Ghobakhloo, 2020). Additionally, I4.0 fosters agile production, customization, and sustainable practices, making the manufacturing sector more competitive and innovative (Hariyani & Mishra, 2022; Sartal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To remain competitive and sustainable, organizations have to orient their competencies, and manufacturing and supply chain (M&SC) practices in line with the requirements of the (1) market, (2) stakeholders, (3) customers and (4) legislation. Through the literature study, it is observed that a sustainable market-focused manufacturing system, that is an integrated sustainable-green-lean-six sigma-agile manufacturing system (ISGLSAMS) is essential to meet all the value metrics of Figure 1 (Hariyani and Mishra, 2022a, b, c, 2023).…”
Section: Introductionmentioning
confidence: 99%